2019
DOI: 10.1002/pmrj.12080
|View full text |Cite
|
Sign up to set email alerts
|

Activity Monitor Placed at the Nonparetic Ankle Is Accurate in Measuring Step Counts During Community Walking in Poststroke Individuals: A Validation Study

Abstract: Background Different environmental factors may affect the accuracy of step‐count activity monitors (AM). However, the validation conditions for AM accuracy largely differ from ecological environments. Objectives To assess and compare the accuracy of AM in counting steps among poststroke individuals: during different locomotor tasks, with AM placed at the nonparetic ankle or hip, and when walking in a laboratory or inside a mall. Design Validation study. Settings Laboratory and community settings. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…The literature reports that the smartphone application placed at the ankle or hip of the non-paretic side during walking did not influence the step count in individuals after chronic stroke during the 6-minute walk test, ramps, or stairs. 28 When the smartphone application was positioned on the non-dominant hand and right pocket, there were no significant differences in step count, regardless of placement, in a study with non-disabled individuals. 21 Thus, the individual should position the device on the most convenient side.…”
Section: Discussionmentioning
confidence: 90%
“…The literature reports that the smartphone application placed at the ankle or hip of the non-paretic side during walking did not influence the step count in individuals after chronic stroke during the 6-minute walk test, ramps, or stairs. 28 When the smartphone application was positioned on the non-dominant hand and right pocket, there were no significant differences in step count, regardless of placement, in a study with non-disabled individuals. 21 Thus, the individual should position the device on the most convenient side.…”
Section: Discussionmentioning
confidence: 90%
“…A total of 90 studies (979 comparisons) examined wearable device step count measurements compared with reference standard criterion measures of manual counting [ 32 , 34 - 38 , 42 , 46 , 47 , 50 - 53 , 57 , 58 , 72 , 80 - 84 , 88 - 102 , 109 , 114 - 125 , 138 - 141 , 144 - 147 , 149 - 153 , 158 - 161 , 165 , 169 - 171 , 173 ] and accelerometry [ 20 , 60 , 64 - 66 , 85 , 103 , 109 , 126 - 128 , 148 , 154 , 164 ] ( Multimedia Appendix 6 ). Of these, 67 studies recruited healthy adults (mean age 35.4 years, SD 17.4 years), 20 studies recruited adults living with limited mobility/chronic diseases (mean age 60.1 years, SD 10.5 years), two studies recruited children living with limited mobility/chronic diseases (mean age 12.5 years, SD 2.9 years), and one study recruited healthy children (mean age 3.7 years, SD 0.6 years).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (51 comparisons) with sample sizes ranging from 13 [ 117 , 138 ] to 56 [ 151 ] reported on interdevice reliability for step count [ 50 , 58 , 72 , 85 , 94 , 110 , 113 , 116 , 117 , 121 , 125 , 138 , 151 , 161 , 171 ]. The majority of correlation coefficients for step count interdevice reliability were very strong (n=35), with only a small number (n=3) being reported as strong.…”
Section: Resultsmentioning
confidence: 99%
“…Using terminology set out in the V3 framework [ 35 ], the problem is not in the verification of the sensor itself, but rather lies in the analytic and clinical validation of the algorithm. People seeking rehabilitation services often do not move normally, such that the algorithms programmed into consumer-grade devices are inaccurate in identifying or quantifying their movement [ 36 , 37 , 38 , 39 , 40 , 41 ]. Continuing with our mainstream metric of walking performance, steps/day has been evaluated across many consumer-grade devices.…”
Section: The Current Situation With Wearable Device Systemsmentioning
confidence: 99%
“…There was wide variability in the accuracy of these devices in individuals with normal gait speed [ 42 , 43 ]. Furthermore, in individuals who utilize assistive devices (e.g., cane, walker) [ 44 , 45 , 46 ], walk with slower speeds (e.g., < 0.8 m/s) [ 36 , 37 , 38 , 39 , 40 , 41 ], or have interruptions in continuous walking [ 47 , 48 ], even higher levels of inaccuracy have been identified. The Fit-Bit Ultra (Fitbit Inc., San Francisco, CA, USA) consumer-level device, for example, has been shown to systematically under-estimate steps for individuals with a diagnosis of stroke and traumatic brain injury over a 2-min walk test, with greater inaccuracy for those who took less steps per minute and those that walked ≤ 0.58 m/s [ 41 ].…”
Section: The Current Situation With Wearable Device Systemsmentioning
confidence: 99%